Induction of mutation in Neurospora crassa with ultraviolet radiation and evaluation of cellulase and xylanase activities - Rahim, Tahsina; Ray, Apurba Lal; Beauty, Salina Parvin; Gomes, Donald James (Bangladesh Journal of Botany, 2010)
Wild Neurospora crassa (Ema) showed highest cellulase activity (0.063 IU) followed by mutants trp 101 (0.055) and leu 299 (0.024). In case of xylanase activity, mutant leu 299 showed highest (0.323) followed by wild (0.310) and mutant trp 101 (0.259). Key words: Neurospora crassa; Mutants; Cellulase activity; Xylanase activity DOI: 10.3329/bjb.v38i2.5149 Bangladesh J. Bot. 38(2): 201-203, 2009 (December)